2018
DOI: 10.1021/acsnano.8b00596
|View full text |Cite
|
Sign up to set email alerts
|

Multifarious Biologic Loaded Liposomes that Stimulate the Mammalian Target of Rapamycin Signaling Pathway Show Retina Neuroprotection after Retina Damage

Abstract: A common event in optic neuropathies is the loss of axons and death of retinal ganglion cells (RGCs) resulting in irreversible blindness. Mammalian target of rapamycin (mTOR) signaling pathway agonists have been shown to foster axon regeneration and RGC survival in animal models of optic nerve damage. However, many challenges remain in developing therapies that exploit cell growth and tissue remodeling including (i) activating/inhibiting cell pathways synergistically, (ii) avoiding tumorigenesis, and (iii) ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…A study on premature rats suggests that this effect may be due to suppressed mTOR signaling in the hippocampus [51]. Experimental upregulation of mTOR signaling promotes retinal ganglion cell survival and axon regeneration after optic nerve crush injury [52,53]. Zhang and coauthors [54] demonstrated a critical role of muscle mTOR catalytic activity in the regulation of whole-body growth and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…A study on premature rats suggests that this effect may be due to suppressed mTOR signaling in the hippocampus [51]. Experimental upregulation of mTOR signaling promotes retinal ganglion cell survival and axon regeneration after optic nerve crush injury [52,53]. Zhang and coauthors [54] demonstrated a critical role of muscle mTOR catalytic activity in the regulation of whole-body growth and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal ganglion cells were isolated from mES-derived organoids at day 21 of differentiation by magnetic microbead-assisted sorting for Thy1 (CD90). 16 The C90+ cells were replated on laminin-coated 16-well chamber glass slides in RGC medium (Neurobasal medium A, 1× B27, 5 µmol/L Forskolin, 50 ng/mL BDNF, 50 ng/mL CNTF, 1× Glutamax, 1× ITS-X) at 8000 cells per well and cultured for two days before functional assay. For the calcium analysis RGCs were loaded with Fluo-4 AM dye (Thermo Fisher): 1 mmol/L stock solution was diluted in BrainPhys medium to make 1 µmol/L loading solution.…”
Section: Methodsmentioning
confidence: 99%
“…Their findings demonstrated significant experimental upregulation of mTOR signaling promoting RGC survival and axon regeneration after an optic nerve crush injury. 129 …”
Section: Optic Neuropathymentioning
confidence: 99%